Holly eaudiobook - King, Stephen (Simon & Schuster Audio, 2023)
#1 New York Times Bestseller * A New York Times Notable Book * An NPR Best Book of the Year Holly Gibney, one of Stephen King's most compelling and resourceful characters, returns in this chilling "exploration of grief and delusion, just pure undistilled evil" ( New York magazine) as she uncovers the truth behind multiple disappearances in a midwestern town. When Penny Dahl calls the Finders Keepers detective agency, hoping for help locating her missing daughter, Holly Gibney is reluctant to accept the case. Her partner, Pete, has Covid. Her (very complicated) mother has just passed away. And Holly is meant to be on leave. But something in Penny's desperate voice makes it impossible to turn her down. Meanwhile, mere blocks from where Bonnie Dahl disappeared live Professors Rodney and Emily Harris. They are the picture of bourgeois respectability: married octogenarians, devoted to each other, and semi-retired lifelong academics. But they are also harboring a shocking, unholy secret in the basement of their well-kept, book-lined home, one that may be related to Bonnie's disappearance. And it will prove nearly impossible to discover what they are up to...for they are savvy, they are patient, and they are ruthless. Now Holly must summon all of her formidable talents to outthink and outmaneuver these unimaginably depraved and brilliantly disguised adversaries in this chilling and unforgettable masterwork from Stephen King.